Remunerating general practitioners with fees: Between economic incentives and professional norms - Bøgh Andersen, Lotte; Serritzlew, Søren (Scandinavian Journal of Public Administration, 2011)
In all the Scandinavian countries, general practitioners (GPs) are, to a varying degree, remunerated with fee per service. Fees can be powerful economic incentives. However, whether or not GPs respond to these incentives is a point of contention in the literature. Some studies find strong associations between the number of patients and service utilization per patient, and interpret this as evidence of supplier-induced demand, other studies do not. The central claim here is that it may depend on the professional norms. Specifically, we expect GPs to respond to economic incentives only if professional norms (prescriptions for the acceptable actions within a given occupation) are absent or weak. To test this, we compare ordinary consultations, talk therapy and house calls for Danish GPs. Ordinary consultations are regulated by strong professional norms; house calls are regulated by norms of medium strength; and only very weak norms apply to talk therapy. As expected, we find stronger effects of economic incentives when the professional norms are weak and conclude that both economic incentives and professional norms are important factors.